Pandemic-Amplified Material Hardship and Community-Led Support among Marshallese Diasporic Communities in the United States. Issue 3 (16th April 2023) - Hallgren, Emily; Moore, Ramey; Riklon, Sheldon; Alik, Eldon; McElfish, Pearl A.
ABSTRACT: This article explores the experiences of Marshallese diasporic migrants in the United States (U.S.) during the COVID-19 pandemic in relation to material hardship and community-led relief efforts. Focus groups with 53 Marshallese migrants in three states revealed that material hardship, including food and housing insecurity, inadequate healthcare, and difficulty paying bills, intensified among their communities during the pandemic. In response, Marshallese community-based groups provided relief to their fellow community members, including food, cash assistance, and personal protective equipment. The findings fit a pattern of intensified hardship and community-led relief among marginalized communities in the U.S. during the COVID-19 pandemic.